Influencia de la programación neurolingüistica en la competitividad organizacional (2020)
In order to generate communication channels, human beings make use of different types of language but in order to give rise to any type of verbal or nonverbal signal, certain senses that by nature every human being possesses must be activated. Analyze everything that involves wanting to communicate, involves talking about neurolinguistics, a discipline that studies language and the brain, understanding that the basis of the whole process is in the brain connections, where thousands of neural channels are housed Once they form 3 representational systems: central nervous, peripheral nervous and sensory.